The combined effect of USP7 inhibitors and PARP inhibitors in hormone-sensitive and castration-resistant prostate cancer cells - Morra, Francesco (Oncotarget, 2017)
PURPOSE OF THE STUDY: Reduced levels of the tumor suppressor protein CCDC6 sensitize cancer cells to the treatment with PARP-inhibitors. The turnover of CCDC6 protein is regulated by the de-ubiquitinase USP7, which also controls the androgen receptor (AR) stability. Here, we correlated the expression levels of CCDC6 and USP7 proteins in primary prostate cancers (PC). Moreover, we tested the efficacy of the USP7 inhibitors, in combination with PARP-inhibitors as a novel therapeutic option in advanced prostate cancer. EXPERIMENTAL TECHNIQUES: PC cells were exposed to USP7 inhibitor, P5091, together with cycloheximide, to investigate the turnover of the USP7 substrates, AR and CCDC6. As outcome of the AR downregulation, transcription targets of AR and its variant V7 were examined by qPCR. As a result of CCDC6 degradation, the induction of PARP inhibitors sensitivity was evaluated by analyzing PC cells viability and foci formation. We scored and correlated CCDC6 and USP7 expression levels in a prostate cancer tissue microarray (TMA). RESULTS: P5091 accelerated the degradation of AR and V7 isoform affecting PSA, UBE2C, CDC20 transcription and PC cells proliferation. Moreover, P5091 accelerated the degradation of CCDC6 sensitizing the cells to PARP-inhibitors, that acted sinergistically with genotoxic agents. The immunohistochemical analysis of both CCDC6 and USP7 proteins exhibited significant correlation for the intensity of staining (p ≤ 0.05). DATA INTERPRETATION: Thus, CCDC6 and USP7 represent predictive markers for the combined treatment of the USP7-inhibitors and PARP-inhibitors in advanced prostate cancer.